The game of Love and Death - Brockenbrough, Martha (Arthur A. Levine Books, an imprint of Scholastic Inc., 2015)
Antony and Cleopatra. Helen of Troy and Paris. Romeo and Juliet. And now... Henry and Flora. For centuries Love and Death have chosen their players. They have set the rules, rolled the dice, and kept close, ready to influence, angling for supremacy. And Death has always won. Always. Could there ever be one time, one place, one pair whose love would truly tip the balance? Meet Flora Saudade, an African-American girl who dreams of becoming the next Amelia Earhart by day and sings in the smoky jazz clubs of Seattle by night. Meet Henry Bishop, born a few blocks and a million worlds away, a white boy with his future assured -- a wealthy adoptive family in the midst of the Great Depression, a college scholarship, and all the opportunities in the world seemingly available to him. The players have been chosen. The dice have been rolled. But when human beings make moves of their own, what happens next is anyone's guess.